Is there any effect of ESG scores on portfolio performance? Evidence from Europe and Turkey - Emre Zehir; Aslı Aybars (Journal of Capital Markets Studies (JCMS), 2020)
Purpose The purpose of this paper is to examine the performance of portfolios that are constructed based on environmental, social and governance (ESG) scores and consist of stocks located in Europe and Turkey. Design/methodology/approach In order to form the portfolios, firstly all stocks are ranked in a descending way based on ESG-based (ESG, environmental, social and governance) scores, separately. Then, 10% of stocks with the highest scores are included in the "Top" portfolio and 10% of stocks with the lowest scores are included in "Bottom" portfolio and totally performance of eight portfolios are investigated. Finally, capital asset pricing model (CAPM) and Fama-French three-factor model are employed as performance measurement benchmarks. Findings Results obtained from CAPM regression show that using ESG-based scores two portfolios underperform the market index. The results of the three-factor model provide that performances of Bottom ESG and Bottom GOV portfolios outperform the market excess return by 0.57% and 0.53%. The overall findings of this paper indicate that there is no relationship between socially responsible investment (SRI) and portfolio performance. These findings are in line with the efficient market hypothesis which indicates all information is reflected in prices. Originality/value The aim of the study is to provide insight on the question of "whether SRI has any effect on the portfolio performance". As far as the literature review is concerned it is seen that this study provide additional insight by utilizing a longer time span together with data from numerous markets.
Keywords: 330; Socially responsible investment; ESG; Portfolio performance